The monetary integration of northwest Europe during the Roman period - Hellings, BDR (2016)
This thesis presents a study of the monetary integration of northwest continental Europe over the course of the Roman period (c. 50 BC – AD 410). 'Integration' is employed here to describe the relationship, as conveyed by the deposition of material culture, between heterogeneous regions and their inhabitants. In order to examine integration, the study combines an unprecedented amount of data from previous regional studies as well as numerous databases and catalogues to survey coin-finds within and beyond the Roman Empire. It places the coin-finds in the context of settlement development in order to understand the nature of the coin-finds. Several approaches are employed to ensure a foundational and extensive overview of coin-finds in the study-region. The period-based case studies consider the Roman provinces and their environs as a single complex geographical unit, rather than as two separate units as a result of a distinguishable (political) frontier between Rome and the 'other'. However, the case studies identify differences within the study-region and smaller regional variations. A chapter is exploring to highlighting the limitations of the main two coin-find types employed in the thesis. The conclusion builds on the necessary and established overall patterns of coin-finds to provide some examples of how coins may have been used by the inhabitants of the study-region. The final two chapters also tie together the results from the previous period case-studies and use Denmark as a comparative case-study to compare the various degrees of integration of barbaricum and the Roman Empire. This thesis provides a much needed and long awaited overview of the Roman coin-finds from the northwest and seeks to demonstrate its use to future research.